2020
DOI: 10.1177/1045159520905364
|View full text |Cite
|
Sign up to set email alerts
|

Practical Heutagogy: Promoting Personalized Learning in Management Education

Abstract: The purpose of this article is to highlight the benefits to both organizations and individuals in adopting heutagogy within management education to develop individual capability. This conceptual paper is based on a systematic review of the literature relating to heutagogy and learning theory. This article calls for the adoption of heutagogic learning within management education alongside traditional pedagogy and andragogy. It provides a number of practical examples of how heutagogy may be implemented in a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 65 publications
0
19
0
2
Order By: Relevance
“…As an agent of their own learning journey, the student decides regarding their own method of how to learn and what to learn. Similar to the concept outlined by Christensen et al's (2013) models, Stoten (2020) and Patel (2018) reported that higher education students have full autonomy of their learning journey; this contradicts the traditional form of the knowledge-seeking process. This shift develops a substantial sense of responsibility and personal identity because of the personal competency awareness (Blaschke & Hase, 2019;Canning & Callan, 2010).…”
Section: Includedmentioning
confidence: 86%
See 1 more Smart Citation
“…As an agent of their own learning journey, the student decides regarding their own method of how to learn and what to learn. Similar to the concept outlined by Christensen et al's (2013) models, Stoten (2020) and Patel (2018) reported that higher education students have full autonomy of their learning journey; this contradicts the traditional form of the knowledge-seeking process. This shift develops a substantial sense of responsibility and personal identity because of the personal competency awareness (Blaschke & Hase, 2019;Canning & Callan, 2010).…”
Section: Includedmentioning
confidence: 86%
“…This would develop their personal and social skills as demanded by Fourth Industrial Revolution (4IR) (Collins et al, 2010;Ricaurte, 2016). Heutagogy is explained by Stoten (2020) to be collaborative in order to develop engagement skills to be applied in their future workplace. Peeragogy and cybergogy, on the other hand, are known as integrating collaboration in the learning process although their collaborative concepts are different, where peeragogical collaborative learning is able to happen in an offline environment (Mulholland, 2019) and happens through an online environment for cybergogy (Wang & Kang, 2006).…”
Section: Immersive Learning Principlesmentioning
confidence: 99%
“…Since then, the method has spread into curricula in many fields (Lundberg & Winn, 2005). The CM is a Socratic studentled system where students review a case (a story about how an organization faced a specific business problem) and have to think through possible solutions and what they would do in the same situation (Stoten, 2020). Critical thinking is "the ability to make decisions based on data, with its inherent uncertainties and variability" (Holmes et al, 2015).…”
Section: Case Methodsmentioning
confidence: 99%
“…It is becoming commonplace to suggest that learning calls for educational processes to enable students to develop adaptabilities, and possess reflexivity and critical insight (Stoten, 2020). Such commentaries, valid as they may be, tend tacitly to endorse the presenting situation, in focusing on the near-at-hand, and not being much concerned with an inquisitiveness to peer beneath immediate appearances into the Real of the world (Bhaskar et al, 1998).…”
Section: Open Pedagogical Situations For a World Of Contingency And C...mentioning
confidence: 99%